Ursodeoxycholic acid alleviates aortic aneurysm and dissection through the intestinal farnesoid X receptor/ceramide synthase 2 axis - Zhaofeng Zhang; Linfeng Xie; Xinfan Lin; Jian He; Yuling Xie; Jiakang Li; Xinghui Zhuang; Lele Tang; Rumei Xie; Qingsong Wu; Zhihuang Qiu; Liangwan Chen (Communications Biology)
Abstract Aortic aneurysm and dissection (AAD) are severe cardiovascular conditions that carry significant risks and currently lack an effective treatment. Ursodeoxycholic acid (UDCA) can delay the onset of various metabolic diseases such as type 2 diabetes and obesity. However, it remains unclear whether UDCA can delay the onset of AAD. We demonstrated pathological activation of the intestinal Farnesoid X receptor (FXR) in both AAD patients and AAD mice. UDCA significantly suppressed intestinal FXR activation. In vivo experiments demonstrated that knockdown of intestinal FXR in mice using adeno-associated virus (AAV) reduced the incidence of AAD, reduced macrophage infiltration, and improved extracellular matrix degradation. In vitro experiments demonstrated that activating intestinal FXR increases the expression of ceramide synthase 2 (Cers2), which participates in the de novo synthesis of ceramides, and promotes the release of C20 ceramide. C20 ceramide promotes extracellular matrix metalloproteinases (MMPs) release from macrophages, leading to extracellular matrix degradation and contributing to AAD development. Our findings highlight the role of UDCA in reducing AAD incidence, revealing the therapeutic potential of the intestinal FXR/Cers2 axis against AAD.